2012
DOI: 10.1101/gr.134304.111
|View full text |Cite
|
Sign up to set email alerts
|

Guthrie card methylomics identifies temporally stable epialleles that are present at birth in humans

Abstract: A major concern in common disease epigenomics is distinguishing causal from consequential epigenetic variation. One means of addressing this issue is to identify the temporal origins of epigenetic variants via longitudinal analyses. However, prospective birth-cohort studies are expensive and time consuming. Here, we report DNA methylomics of archived Guthrie cards for the retrospective longitudinal analyses of in-utero-derived DNA methylation variation. We first validate two methodologies for generating compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
6
55
0
Order By: Relevance
“…1), suggesting their promise for future clinical application. However, Robinson et al 21,22 found that genetic variation, including single nucleotide contribute to predominantly HCV-related HCC in the US. A total of 130,512 CpG sites across the entire genome significantly differ in methylation levels between HCC tumor and adjacent non-tumor tissues after Bonferroni correction for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…1), suggesting their promise for future clinical application. However, Robinson et al 21,22 found that genetic variation, including single nucleotide contribute to predominantly HCV-related HCC in the US. A total of 130,512 CpG sites across the entire genome significantly differ in methylation levels between HCC tumor and adjacent non-tumor tissues after Bonferroni correction for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…38 Therefore, if possible, profiling both blood and buccals will not be redundant but rather provide complementary information. However, in the case of an EWAS of a non-blood disease/phenotype, if a choice has to be made between the two surrogate tissues, then buccal may be more informative.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Using our methods, we see similarly high-quality TNGS performance of DNA isolated from DBS as compared with the standard 10 ml of whole blood and saliva (Supplementary Figure S1 online). With a control sample set, our protocols yielded ~450 ng doublestranded DNA (dsDNA) from one-half of a single saturated spot from the DBS card, representing 25 µl blood (as measured by the dsDNA-specific Qubit assay; Supplementary Table S2 online).…”
Section: Validation Of Dna Isolation From Minimally Invasive Dbs and mentioning
confidence: 81%